AI and machine learning in the financial sector: Five focus points - Alessandro Martinello; Thais Lærkholm Jensen; Erik Grenestam; Bjørn Bjørnsson Meyer (Danmarks Nationalbank, 2022)
Artificial intelligence (AI) can improve the resiliency of both individual financial institutions and the financial sector as a whole. Yet, its users must balance benefits and risks of these technologies. This paper illustrates five focus points which financial institutions should consider when moving from traditional models to complex AI systems.
Keywords: 330; Financial sector; Risk management; Statistical method; Financial stability